2020
DOI: 10.3390/molecules25020344
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Six Isoflavones from Puerariae Lobatae Radix by CPE-HPLC and Effect of Puerarin on Tyrosinase Activity

Abstract: Tyrosinase inhibitors with excellent inhibitory activities and lower side effects have promising applications in the fields of medicine, agriculture, food sciences and cosmetics. In this study, a method for simultaneous separation and determination of six target compounds (puerarin, daidzin, genistein, daidzein, genistin, and formononetin) in Puerariae Lobatae Radix was established by cloud point extraction (CPE) and concentration combined with high performance liquid chromatography (HPLC). To achieve high ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Moreover, PAs extracted from leaves have a better inhibitory effect on tyrosinase monophenolase activity than those from branches. Qu et al [26] reported the effects of puerarin on the tyrosinase monophenolase activity with an IC 50 value of 0.537 mg/mL. Cui et al [27] reported that T. grandis "Xiangyafei" seed oil (XYSO) exhibited the highest activities in the tested seed oils against tyrosinase monophenolase (IC 50 = 817.5 μg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PAs extracted from leaves have a better inhibitory effect on tyrosinase monophenolase activity than those from branches. Qu et al [26] reported the effects of puerarin on the tyrosinase monophenolase activity with an IC 50 value of 0.537 mg/mL. Cui et al [27] reported that T. grandis "Xiangyafei" seed oil (XYSO) exhibited the highest activities in the tested seed oils against tyrosinase monophenolase (IC 50 = 817.5 μg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, as a common clinical pathological process, is closely related to many diseases such as arthritis, psychosis, cardiovascular and cerebrovascular diseases, and cancer [ 1 ]. Tyrosinase is the key enzyme of melanin synthesis, and its overexpression can lead to pigmentation diseases such as freckles, chloasma and melanoma [ 2 ]. At present, anti-inflammatory drugs such as glucocorticoids, insulin, and tyrosinase inhibitors such as kojic acid have been proven to have significant side effects [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both of them had good inhibitory activity on tyrosinase diphenolase, especially the extract of PAs from leaves of C. camphora. Qu et al (23) reported the effects of puerarin on the monophenolase activity with an IC value of 0.537 mg/mL. Cui et al ( 9) reported that T. grandis "Xiangyafei" seed oil (XYSO) exhibited the highest activities in the tested seed oils against tyrosinase monophenolase ( IC 50 = 817.5 μg/mL).…”
Section: Effect Of C Camphora Pas On the Activity Of Tyrosinase Monomentioning
confidence: 99%